Efficacy of lung ultrasound and chest X-ray in children with cough and fast breathing to search a prognostic diagnostic approach to predict childhood pneumonia - Shaik Md Sajid Basha; Murali Krishnaiah D; Shaik Abdul Khaleef; Zia Ur Rahman (Amaltea Medical Publishing House, 2023)
Background. Globally, pneumonia is one of the major cause of mortality and morbidity in children aged below 5 years. Lung ultrasonography (LUS) may become the next line investigation of choice before CXR and CT. Researchers have investigated the idea of employing LUS to diagnose pneumonia. Aim. To evaluate the findings of LUS in children with pneumonia and to correlate LUS findings with clinical and etiological findings in children. Methods. Study conducted in 100 children with chronic cough and fast breathing. All children undergone LUS within 24 hrs, and the data was correlated between clinical indicators and ultrasound proven pneumonia. The ROC (receiver operating characteristic curve) was drafted to estimate the cut-off values for respiratory, and laboratory variables. Results. 44% had positive LUS results. The presence of sensitivity with 88.5%, 77.45%, 95.4%, 81.6%, 79.4%, 70.45%, 84.25%, and 86.25% for the presence of fever, refusal of feeds/fluids, temperature 380C, oxygen saturation 95%, nasal flaring, grunting, chest retractions, and crepitation in children to predict the pneumonia. Leukocytosis appeared in 60% and CRP positive in 24% children. Grunting had the highest specificity of 94.66%. Chest x-ray identified 40% of pneumonia cases, while LUS identified 44% pneumonia cases. LUS had a sensitivity of 0.895 and a specificity of 0.66, and CXR had a sensitivity of 0.855 and a specificity of 0.60 to detect pneumonia. Conclusions. LUS cannot be used a sole diagnostic tool in childhood pneumonia, but it has role in the detection of complications. LUS has higher diagnostic accuracy than CXR for pneumonia diagnosis.